Progesterone: A Hope to Prevent Preterm Births & Reduce Perinatal Mortality - Tanzila Rafiq, Naheed Hayat, Syeda Uzma, Maria Masher, Naheed Fatima, Piya Muhammad Musammat Rafi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To assess and compare the maintenance of tocolysis in preterm labor by using vaginal and intramuscular progesterone. Study design: Randomized controlled trial. Settings and study duration: Department of Obstetrics & Gynecology, Civil Hospital, Bahawalpur between 12th March 2019 and 11th September 2019 Materials & Methods: A total of 96 women ranging from 18 and 40 years of age presented with threatened preterm labour, at gestational age between 28 to 36 weeks were included. Out of total, Patients having multiple pregnancy, preterm premature rupture of membrane, medical disorders, IUGR and APH were excluded .All patients were given acute tocolytic therapy with oral nifedipine. Then they were divided in 2 groups. In the Group A, vaginal progesterone (Cyclogest 200mg) was given daily while in group B patients, a single intramuscular injection(IM) of 250 mg of 17-alpha-hydroxyprogesterone caproate (17 OHP) was given weekly. All patients in both groups were evaluated upto the delivery and efficacy was documented. Results: The mean age was 29.34 ± .4.92 years. The gestational age was from 28 to 36 weeks with mean age of 30.91 ± 1.44 weeks. Efficacy ( no preterm birth) was seen in 42 (87.50%) in group A (vaginal progesterone) and 34 (70.83%) in group B (intramuscular progesterone) with p-value of 0.044. Conclusion: The verdict of the study is that for preventing preterm birth the efficacy of vaginal progesterone is better than intramuscular. Keywords: vaginal progesterone, preterm birth, perinatal mortality, preterm labour, hydroxyprogesterone, tocolytic maintenance.